IN SILICO INTERACTION STUDIES OF RESVERATROL AND SILIBININ WITH DIFFERENT PROTEIN TARGETS USING MOLECULAR DOCKING - J. Venkatesh Yadav; G. V. Sudhakar Rao; N. Pazhanivel; P.L. Sujatha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Resveratrol and silibinin are natural phytochemicals with considerable anticancer properties. They induce apoptosis of cancer cells by binding to various protein targets. Hence in this study, in silico molecular interaction studies were made between ligand resveratrol and ligand silibinin with NF-kB p50 subunit and p65 subunit, MMP9, caspase 3 and Bax proteins. The in silico molecular interaction revealed that silibinin and resveratrol interacted with five receptors with a high binding affinity and docking score making them novel inhibitors against various types of diseases.